PENGARUH SARANA PRASARANA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEMADAM KEBAKARAN KOTA BEKASI - Edward Efendi Silalahi; Laila Syahri Nurkharimah (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to determine the effect of infrastructure and workload on employee performance at the Bekasi City Fire Department. The method used in this study is a quantitative method, where the object used is the employees of the Bekasi City Fire Department. The number of samples used in this study were 60 respondents using a non-probability sampling technique with a saturated sampling technique. This study uses primary data conducted in distributing questionnaires to employees at the Bekasi City Fire Department. After the data is collected, the data is processed using the SPSS 25 for windows program. Based on the results of the analysis carried out, it can be concluded that the infrastructure and workload variables partially have a positive and significant effect on employee performance. Then, simultaneously the variables of Infrastructure and Workload partially have a positive and significant effect on employee performance